Late Effects of Low-Dose Radiation on the Bone Marrow, Lung, and Testis Collected From the Same Exposed BALB/cJ Mice - Witawat Jangiam; Chatchanok Udomtanakunchai; Paiboon Reungpatthanaphong; Montree Tungjai; Louise Honikel; Chris R. Gordon; Kanokporn Noy Rithidech (SAGE Publishing, 2018)
We used 3 biological metrics highly relevant to health risks, that is, cell death, inflammation, and global DNA methylation, to determine the late effects of low doses (0.05 or 0.1 Gy) of 137 Cs γ rays on the bone marrow, lung, and testis collected at 6 months post-irradiation from the same exposed BALB/cJ mouse. This integrative approach has not been used for such a purpose. Mice exposed to 0 or 1 Gy of radiation served as a sham or positive control group, respectively. The results could deliver information for better health risk assessment across tissues, including better scientific basis for radiation protection and clinical application. We found no changes in the levels of all studied biological metrics (except a significant increase in the levels of an anti-inflammatory cytokine, ie, interleukin 10) in tissues of 0.05-Gy exposed mice, when compared to those in sham controls. In contrast, significantly increased levels of cell death and inflammation, including a significant loss of global 5-hydroxymethylcytosine, were found in all tissues of the same mice exposed to 0.1 or 1.0 Gy. Our data demonstrated not only no harm but also hormesis in the 0.05-Gy exposed mice. However, the hormetic effect appears to be dependent on biological metrics and tissue.